2002
DOI: 10.3928/0098-9134-20020601-08
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Aggressive, Agitated, or Disruptive Behavior: PARTICIPATION IN A BEHAVIOR MANAGEMENT UNIT

Abstract: A 32-bed Behavior Management Unit was opened in a long-term care facility to care for dementia patients who exhibit aggressive, agitated, or disruptive (AAD) behaviors. The purpose of the study was to evaluate the effectiveness of the Behavior Management Program (BMP) in decreasing such behaviors. The sample consisted of all patients (N = 32) who resided in the unit for at least 3 months. The Nursing Home Behavior Problem Scale (NHBPS) was used to collect data. Hypothesis 1, predicting participation in the BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…The two most important outcomes reported were a decrease in the levels of general psychiatric symptoms (especially depression and agitation or aggression) (Brodaty et al, 2003;DeYoung et al, 2002;Holm et al, 1999;Kunik et al, 1996;Opie et al, 2002;Proctor et al, 1999;Rovner et al, 1996;Wiener et al, 2001) and improvement in global functioning (cognitive and functional status) (Holm et al, 1999;Kunik et al, 1996;Wiener et al, 2001). One of the four randomized controlled trials, which examined these outcomes, found no significant difference between nursing home patients who received psychiatric services and a comparison group that received care as usual.…”
Section: Reported Outcomes Of Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The two most important outcomes reported were a decrease in the levels of general psychiatric symptoms (especially depression and agitation or aggression) (Brodaty et al, 2003;DeYoung et al, 2002;Holm et al, 1999;Kunik et al, 1996;Opie et al, 2002;Proctor et al, 1999;Rovner et al, 1996;Wiener et al, 2001) and improvement in global functioning (cognitive and functional status) (Holm et al, 1999;Kunik et al, 1996;Wiener et al, 2001). One of the four randomized controlled trials, which examined these outcomes, found no significant difference between nursing home patients who received psychiatric services and a comparison group that received care as usual.…”
Section: Reported Outcomes Of Interventionsmentioning
confidence: 99%
“…Three of the four remaining studies used only psychological and/or neuropsychological and psychiatric examinations (2001) Opie (2002) DeYoung (2002) Brodaty (2003) ( Opie et al, 2002;Proctor et al, 1999;Rovner et al, 1996). The other study (DeYoung et al, 2002) does not clearly describe the examinations performed. Wiener also performed a nursing assessment of each patient's activities in daily life, while Kunik, Holm and Wiener examined the global functioning of all patients.…”
Section: Characteristics Of Interventionsmentioning
confidence: 99%
See 3 more Smart Citations